Material suitable for deepwater bending intensifier and forming method of material
By introducing multi-scale reinforcement phases and specific forming methods into deep-water bending reinforcers, the problem of insufficient performance under the coupling effect of multi-physics in the prior art is solved, and the tensile strength and anti-aging performance of bending reinforcers are significantly improved.
Patent Information
- Application Number
- CN202411759329.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
AI Technical Summary
The existing deep-water bending reinforcers lack performance under the multi-physical coupling effects such as ultraviolet, aging, salt spray and fatigue loads, resulting in fatigue damage or buckling deformation at the riser and cable joints, reducing service life.
By adopting multi-scale strengthening technology, by introducing materials such as polyether prepolymers, mochas, chopped fibers and silica particles, materials for bending reinforcers suitable for deep water environments are formed, and specific forming methods are adopted, such as vacuum drying, ultrasonic stirring and vacuum defoaming, bending reinforcers with improved tensile strength and anti-aging properties are prepared.
By introducing multi-scale reinforcement phases, the tensile strength of the bending reinforcement is increased by 20%, and the tensile performance against UV aging is improved by 10%, which significantly improves the comprehensive performance under the coupling effect of multi-physics fields.
Abstract
Description
Technical Field
[0001] The invention relates to the field of material forming technology, and in particular to a material suitable for a deep-water bending reinforcer and a forming method thereof. Background Art
[0002] The transmission of submarine oil and gas mainly relies on underwater oil pipelines. During the working process, the oil and gas transmission pipeline is subjected to the coupling of multiple fields such as internal transmission medium and underwater eddy current and surge, which is prone to damage and destruction. Especially at the interface of the oil pipeline and the oil storage device, the effect of wind and wave current causes fatigue damage or buckling deformation at the interface of the deepwater pipeline and the cable under the action of reciprocating load, which greatly reduces the service life of the riser and cable. The application of deepwater riser bending stiffener improves the fatigue resistance of the riser and cable joints and increases the service life of the riser or cable. The existing bending stiffener is mainly made of polyurethane material, which has certain viscoelastic properties and good fatigue resistance. However, under the coupling of multiple physical fields such as ultraviolet, aging, salt spray, fatigue load, etc., to achieve further improvement of product performance, disadvantages are revealed. Polyurethane is a polymer material made by the polymerization reaction of polyols and polyisocyanates. Different structures and properties can be obtained through different raw materials. It can be prepared into various products such as coatings, adhesives, plastics, fibers, rubbers, etc. from liquid to solid, from soft to hard. Polyurethane hardener has excellent toughness, impact resistance, wear resistance and tear resistance. The polyurethane processing and molding process is simple, and injection, casting and other processes can achieve good molding effects, so it is widely used and its application range is growing rapidly. In order to improve the comprehensive performance of the riser bending stiffener under the coupling of multiple physical fields such as ultraviolet, aging, salt spray, and fatigue loads, the present invention proposes a multi-scale strengthening technical approach and a molding process for multi-size strengthening modified materials. The bending stiffener prepared with modified materials is more suitable for deepwater environments and sea conditions. Summary of the invention
[0003] The purpose of the present invention is to address the deficiencies of the prior art and provide a material suitable for deepwater bending stiffeners and a forming method thereof, so as to improve the mechanical and aging properties of deepwater bending stiffeners, thereby ensuring the safe and stable operation of underwater pipelines. To achieve the above purpose, the technical solution adopted by the present invention is:
[0004] A material suitable for a deep-water bending reinforcer comprises 90-110 parts of a polyether prepolymer, 15-25 parts of mocha, 23-28 parts of short-cut fibers and 1-3 parts of silicon dioxide particles.
[0005] The invention discloses a material suitable for a deep-water bending reinforcer. The material comprises 95-105 parts of a polyether prepolymer, 18-23 parts of mocha, 24-26 parts of short-cut fibers and 2 parts of silicon dioxide particles.
[0006] The invention discloses a material suitable for a deep-water bending reinforcer. The material comprises 100 parts of a polyether prepolymer, 18 parts of mocha, 25 parts of chopped fibers and 2 parts of silicon dioxide particles.
[0007] The invention discloses a material suitable for a deep-water bending reinforcer. The chopped fibers are carbon fibers with a size of 40-50 microns.
[0008] The invention discloses a material suitable for a deep-water bending reinforcer, wherein the size of the silicon dioxide particles is 28-32 nanometers.
[0009] A forming method for a material used for a deepwater bending stiffener, comprising the following specific steps:
[0010] Step 1: First, dry the polyether prepolymer and mocha in a vacuum drying oven at 85-95°C for 2-3 hours and set aside;
[0011] Step 2: Then stir and mix the chopped fibers, silica particles and the polyether prepolymer dried in step 1 to form a mixture, stir for 30-40 minutes, and set aside;
[0012] Step 3: Keep the mocha dried in step 1 at 120-130°C for 15 minutes to melt it for later use;
[0013] Step 4: Preheat the bending stiffener mold at 130°C for 30 minutes and set aside;
[0014] Step 5: Mix the melted mocha in step 3 with the mixture in step 2, stir for 2-8 minutes, cast into the mold in step 4, cool to 90-95°C and start vacuum degassing for 5-10 minutes;
[0015] Step 6: Finally, the mold in step 5 is cured at 130°C for 1-2 hours, demolded and matured, and cooled in the furnace.
[0016] The present invention provides a forming method suitable for a material for a deep-water bending reinforcer. In the step 1, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95° C. for 2 hours.
[0017] The present invention provides a forming method suitable for a material for a deepwater bending reinforcer. In the second step, the chopped fibers, the silica particles and the polyether prepolymer are stirred and mixed under an ultrasonic environment to form a mixture, and the ultrasonic stirring time is 30 minutes;
[0018] The present invention provides a forming method suitable for a material used for a deep-water bending reinforcer. In the step 5, the mocha is mixed with the mixture in the step 2 and ultrasonically stirred for 2-8 minutes.
[0019] The present invention provides a forming method suitable for a material for a deepwater bending reinforcer, wherein the step six is to cure the material at a temperature of 100-120° C. for 16-20 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects: a multi-scale reinforcement phase is introduced in the polyurethane molding process, and the tensile strength of the bending reinforcer is increased by up to 20%, and the anti-ultraviolet aging tensile performance is increased by up to 10% through the introduction of chopped fibers and granular materials. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1: A material suitable for deep-water bending reinforcers, characterized in that the material suitable for deep-water bending reinforcers comprises 90-110 parts of polyether prepolymer, 15-25 parts of mocha, 23-28 parts of chopped fibers and 1-3 parts of silica particles.
[0023] Preferably, the polyether prepolymer is 95-105 parts, the mocha is 18-23 parts, the short-cut fibers are 24-26 parts and the silica particles are 2 parts.
[0024] Preferably, the polyether prepolymer is 100 parts, the mocha is 18 parts, the short-cut fibers are 25 parts, and the silica particles are 2 parts.
[0025] Preferably, the chopped fibers are carbon fibers with a size of 40-50 microns.
[0026] The silica particle size is 28-32 nanometers.
[0027] A forming method for a material used for a deepwater bending stiffener, comprising the following specific steps:
[0028] Step 1: First, dry the polyether prepolymer and mocha in a vacuum drying oven at 85-95°C for 2-3 hours and set aside;
[0029] Step 2: Then stir and mix the chopped fibers, silica particles and the polyether prepolymer dried in step 1 to form a mixture, stir for 30-40 minutes, and set aside;
[0030] Step 3: Keep the mocha dried in step 1 at 120-130°C for 15 minutes to melt it for later use;
[0031] Step 4: Preheat the bending stiffener mold at 130°C for 30 minutes and set aside;
[0032] Step 5: Mix the melted mocha in step 3 with the mixture in step 2, rotate and stir for 2-8 minutes, cast into the mold in step 4, cool to 90-95°C and start vacuum degassing for 5-10 minutes;
[0033] Step 6: Finally, the mold in step 5 is cured at 130°C for 1-2 hours, demolded and matured, and cooled in the furnace.
[0034] Preferably, in the step 1, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95° C. for 2 hours.
[0035] Preferably, in the step 2, the chopped fibers, the silica particles and the polyether prepolymer are stirred and mixed under an ultrasonic environment to form a mixture, and the ultrasonic stirring time is 30 minutes;
[0036] Preferably, the mocha in step 5 is mixed with the mixture in step 2 and ultrasonically stirred for 2-8 minutes.
[0037] Preferably, in the step five, the mocha melted in the step three and the mixture in the step two are mixed, and ultrasonically and mechanically stirred for 5 minutes.
[0038] Preferably, in step six, the aging is carried out at a temperature of 100-120° C. for 16-20 hours.
[0039] Preferably, in step six, the aging is carried out at 100° C. for 18 hours.
[0040] Preferably, in step six, the sample is aged at 100° C. for 18 hours and then cooled at room temperature.
[0041] Example 2: A material suitable for deep-water bending reinforcers and a forming method thereof, comprising 100 parts of polyether prepolymer, 18 parts of mocha, 25 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then the mixture is stirred and mixed with the chopped fibers, silica particles, and the polyether prepolymer to form a mixture, which is stirred mechanically and ultrasonically for 30 minutes, and then the mixture is stirred at 130°C for 15 minutes, and then the mixture is melted and then the mixture is stirred at 130°C for 30 minutes, and then the mixture is stirred mechanically for 5 minutes, and then the mixture is cast into the preheated mold, and then the mixture is cooled to 90°C and vacuum degassing is started for 5 minutes, and then the degassing time is 5 minutes, and finally, the mixture is cured at 130°C for 1 hour, and then the mixture is demolded and aged at 120°C for 16 hours, and then cooled with the furnace.
[0042] Example 3: A material suitable for deep-water bending reinforcers and its forming method, comprising 100 parts of polyether prepolymer, 18 parts of mocha, 25 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then the mixture is stirred and mixed with the chopped fibers, silica particles, and the polyether prepolymer to form a mixture, and the mixture is stirred mechanically and ultrasonically for 30 minutes, and then the mixture is stirred and mixed; the mocha is kept at 130°C for 15 minutes, melted, and then the mixture is stirred and mixed; the mold is preheated at 130°C for 30 minutes, and then the mixture is stirred and mixed; the mixture is mixed with the mixture, mechanically rotated and stirred for 5 minutes, and then cast into the preheated mold, and then cooled to 90°C for vacuum degassing, and the degassing time is 5 minutes; finally, the mixture is demolded and aged at 110°C for 20 hours, and then cooled with the furnace.
[0043] Example 4: A material suitable for deep-water bending reinforcers and its forming method, comprising 100 parts of polyether prepolymer, 18 parts of mocha, 25 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then the mixture is stirred and mixed with the chopped fibers, silica particles and polyether prepolymer to form a mixture, and the mixture is stirred mechanically and ultrasonically for 30 minutes, and then the mixture is stirred; the mocha is kept at 130°C for 15 minutes, melted, and then the mixture is melted; the mold is preheated at 130°C for 30 minutes, and then the mixture is stirred mechanically for 5 minutes, and then the mixture is cast into the preheated mold, and then the mixture is cooled to 90°C for vacuum degassing, and the degassing time is 5 minutes; finally, the mixture is demolded and aged at 120°C for 20 hours, and then cooled at room temperature.
[0044] The modified polyurethane components obtained in Examples 2-4 were tested for mechanical properties and aging properties using the same batch. The test results showed that the room temperature tensile strength reached 11.3 MPa, and the tensile strength was 10.2 MPa after seven days of UV aging. The tensile strength of the sample increased by 20% and the aging resistance increased by 10%.
[0045] Example 5: A material suitable for deep-water bending reinforcers and a forming method thereof, comprising 110 parts of polyether prepolymer, 20 parts of mocha, 26 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then the mixture is stirred and mixed with the chopped fibers, silica particles, and the polyether prepolymer to form a mixture, and the mixture is stirred mechanically and ultrasonically for 30 minutes, and then the mixture is stirred; the mocha is kept at 130°C for 15 minutes, melted, and then the mixture is melted; the mold is preheated at 130°C for 30 minutes, and then the mixture is stirred mechanically for 5 minutes, and then the mixture is cast into the preheated mold, cooled to 90°C, and vacuum degassing is started for 5 minutes; finally, after curing at 130°C for 1 hour, the mixture is demolded and aged at 130°C for 16 hours, and then cooled with the furnace.
[0046] The modified polyurethane component obtained in Example 5 was tested for mechanical properties and aging properties using the same batch. The test results showed that the room temperature tensile strength reached 9.50 MPa, and the tensile strength was 8.33 MPa after seven days of UV aging. The tensile strength of the sample increased by 10%, and the aging resistance increased by 10%.
[0047] Example 6: A material suitable for deep-water bending reinforcers and a forming method thereof, comprising 90 parts of polyether prepolymer, 16 parts of mocha, 23 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then the mixture is stirred and mixed with the chopped fibers, silica particles, and the polyether prepolymer to form a mixture, which is stirred mechanically and ultrasonically for 30 minutes, and then the mixture is stirred at 130°C for 15 minutes, and then the mixture is melted and then the mixture is stirred at 130°C for 30 minutes, and then the mixture is stirred mechanically for 5 minutes, and then the mixture is cast into the preheated mold, and then the mixture is cooled to 90°C and vacuum degassing is started for 5 minutes, and then the degassing time is 5 minutes, and finally, the mixture is cured at 130°C for 1 hour, and then the mixture is demolded and aged at 110°C for 20 hours, and then cooled with the furnace.
[0048] The modified polyurethane component obtained in Example 6 was tested for mechanical properties and aging properties using the same batch. The test results showed that the room temperature tensile strength reached 9.0 MPa, and the tensile strength was 7.8 MPa after seven days of UV aging. The tensile strength of the sample increased by 4% and the aging resistance increased by 9%.
[0049] Example 7: A material suitable for deep-water bending reinforcers and a forming method thereof, comprising 100 parts of polyether prepolymer, 18 parts of mocha, 25 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours and then set aside; then the chopped fibers, silica particles and polyether prepolymer are stirred and mixed to form a mixture, which is mechanically rotated and stirred for 30 minutes and set aside; the mocha is kept at 130°C for 15 minutes and melted for set aside; the mold is preheated at 130°C for 30 minutes and set aside; the mocha and the mixture are mixed, mechanically rotated and stirred for 5 minutes, and then cast into the preheated mold, cooled to 90°C and vacuum degassing is started for 5 minutes; finally, after curing at 130°C for 1 hour, demolded at 110°C and aged for 20 hours, and cooled with the furnace.
[0050] Example 8: A material suitable for deep-water bending reinforcers and a forming method thereof, with 90 parts of polyether prepolymer, 16 parts of mocha, 23 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then stand by; then the chopped fibers, silica particles and polyether prepolymer are stirred and mixed to form a mixture, and the mixture is mechanically rotated and stirred for 30 minutes, and then stand by; the mocha is kept at 130°C for 15 minutes, melted, and then stand by; the mold is preheated at 130°C for 30 minutes, and then stand by; the mocha and the mixture are mixed, mechanically rotated and stirred for 5 minutes, and then cast into the preheated mold, cooled to 90°C and vacuum degassing is started, and the degassing time is 5 minutes; finally, after curing at 130°C for 1 hour, demolded at 110°C for 20 hours, and cooled with the furnace.
[0051] Example 9: A material suitable for deep-water bending reinforcers and a forming method thereof, with 110 parts of polyether prepolymer, 20 parts of mocha, 23 parts of chopped fibers, and 2 parts of silica particles. First, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95°C for 2 hours, and then stand by; then the chopped fibers, silica particles and polyether prepolymer are stirred and mixed to form a mixture, and the mixture is mechanically rotated and stirred for 30 minutes, and then stand by; the mocha is kept at 130°C for 15 minutes, melted, and then stand by; the mold is preheated at 130°C for 30 minutes, and then stand by; the mocha and the mixture are mixed, mechanically rotated and stirred for 5 minutes, and then cast into the preheated mold, cooled to 90°C and vacuum degassing is started, and the degassing time is 5 minutes; finally, after curing at 130°C for 1 hour, demolded at 110°C for 20 hours, and cooled with the furnace.
[0052] The modified polyurethane components obtained in Examples 7-9 contained a large number of bubbles inside, and the mechanical properties and UV aging properties could not be measured.
[0053] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A material suitable for deepwater bending stiffeners, characterized in that: The material suitable for deep-water bending reinforcers comprises 90-110 parts of polyether prepolymer, 15-25 parts of mocha, 23-28 parts of short-cut fibers and 1-3 parts of silicon dioxide particles.
2. The material for deepwater bending stiffener according to claim 1, characterized in that: The polyether prepolymer is 95-105 parts, mocha is 18-23 parts, short-cut fibers are 24-26 parts and silica particles are 2 parts.
3. The material for deepwater bending stiffener according to claim 1, characterized in that: The polyether prepolymer is 100 parts, mocha is 18 parts, short-cut fibers are 25 parts, and silica particles are 2 parts.
4. The material for deepwater bending stiffener according to claim 1, characterized in that: The chopped fibers are carbon fibers with a size of 40-50 microns.
5. The material for deepwater bending stiffener according to claim 1, characterized in that: The silica particles have a size of 28-32 nanometers.
6. A forming method for a material for a deepwater bending stiffener as claimed in claims 1 to 5, characterized in that: The specific steps are: Step 1: First, dry the polyether prepolymer and mocha in a vacuum drying oven at 85-95°C for 2-3 hours and set aside; Step 2: Then stir and mix the chopped fibers, silica particles and the polyether prepolymer dried in step 1 to form a mixture, stir for 30-40 minutes, and set aside; Step 3: Keep the mocha dried in step 1 at 120-130°C for 15 minutes to melt it for later use; Step 4: Preheat the bending stiffener mold at 130°C for 30 minutes and set aside; Step 5: Mix the melted mocha in step 3 with the mixture in step 2, stir for 2-8 minutes, cast into the mold in step 4, cool to 90-95°C and start vacuum degassing for 5-10 minutes; Step 6: Finally, the mold in step 5 is cured at 130°C for 1-2 hours, demolded and matured, and cooled in the furnace.
7. The forming method of the material for deepwater bending stiffener according to claim 6, characterized in that: In the step 1, the polyether prepolymer and mocha are dried in a vacuum drying oven at 95° C. for 2 hours.
8. The forming method of the material for deepwater bending stiffener according to claim 6, characterized in that: In the step 2, the chopped fibers, the silica particles and the polyether prepolymer are stirred and mixed under an ultrasonic environment to form a mixture, and the ultrasonic stirring time is 30 minutes.
9. The forming method of the material for deepwater bending stiffener according to claim 6, characterized in that: The mocha in step 5 is mixed with the mixture in step 2, and ultrasonically stirred for 2-8 minutes.
10. The forming method of the material suitable for deep-water bending stiffener according to claim 6, characterized in that: In the step six, the mixture is aged at 100-120° C. for 16-20 hours.
Citation Information
Patent Citations
Polyurethane / foamed aluminum composite material and preparation method thereof
CN104439166A
Polyurethane robot and preparation method thereof
CN105237732A
Abrasion-resistant polyurethane elastomer material and method for manufacturing pump parts by using same
CN110317315A
Nanofiber-particle composite reinforced high-modulus polyurethane composite material and preparation method thereof
CN116496517A
Multi-scale design nylon reinforced polyurethane composite material and preparation method thereof
CN118772619A